Beyond nets and sprays: transformative strategies for malaria resilience in Sub-Saharan Africa - Mwang'onde, Beda John (Journal of Health & Biological Sciences, 2024)
Objective: This narrative review assesses the effectiveness of malaria interventions in Sub-Saharan Africa in alignment with the World Health Organization's (WHO) Global Technical Strategy for Malaria 2016–2030. Methods: Literature searches utilized WHO malaria reports from 2015 to 2023, along with published articles from databases including Springer, Hindawi, PubMed, Google Scholar, BioMed, and Elsevier. Results: The review highlights that interventions such as habitat modification and house improvements are effective, particularly in addressing human-related factors in mosquito breeding. However, challenges persist in epidemic preparedness, diagnostic methods, and malaria research, all of which are crucial for effective management. Weak healthcare systems, limited funding, and insufficient surveillance capabilities further undermine malaria control strategies in Sub-Saharan Africa. The importance of research and innovation especially from scientists within malaria-affected regions is emphasized as vital to achieving malaria elimination. Coordinated efforts, alongside substantial investments in basic science and implementation research, are also essential. Despite these obstacles, recent success in malaria elimination in China illustrates the feasibility of control and eradication through well-coordinated initiatives. Conclusion: modifying houses is one of the simplest and most eco-friendly strategies to control indoor malaria transmission. However, achieving sustainable progress in malaria control across Sub-Saharan Africa demands a comprehensive, collaborative, and adaptive approach. This review highlights the need for diverse and innovative strategies to meet the goals set forth by the WHO Global Technical Strategy.